IMPLEMENTASI PERDA NO 11 TAHUN 2000 TENTANG KEBIJAKAN PENGATURAN DAN PEMBINAAN PKL di KELURAHAN KARANGTEMPEL KECAMATAN SEMARANG TIMUR KOTA SEMARANG - Ardiyana Nisafatul Irma; Aloysius Rengga; Aufarul Marom (Journal of Public Policy and Management Review, 2015)
The existence of street vendors (PKL) in Semarang which increases every year makes Semarang government seeks to make arrangements and coaching. Form of regulation and guidance through Regulation No. 11 of 2000. This was done in view of the presence of street vendors, especially in Sub Karangtempel Eastern District of Semarang contribute to regional revenue by withdrawal retribution. However, the existence of the street vendors also disturb the cleanliness, the road scenery, or even sometimes cause traffic jams as street vendors put merchandise in vain. Problems studied related to how the implementation of Regulation No. 11 of 2000 and inhibiting factors in the implementation of Regulation No. 11 of 2000. This study uses descriptive qualitative research methods. The technique of collecting data by in-depth interviews, documentation and observation studies.The results showed that the implementation of Regulation No. 11 of 2000 on the policy setting and street vendors development at village Karangtempel Eastern District of Semarang still not going well. This is can be viewed from the mechanism of implementation of Regulation No. 11 of 2000 experienced overlapping authority and are still violations committed by street vendors to Regulation No. 11 of 2000. The violations occurred among street vendors who put merchandise on the patio or sidewalks, street vendors permanent buildings along East Flood Canal river, non-compliance in the street vendors pay the levy. Inhibiting factors encountered in the field is limited funding sources, awareness of vendors to Regulation No. 11 of 2000 is still low, and so the firmness of the implementor. So that the implementor need to consider factors such as resources, communications, disposition and bureaucratic structures so that the implementation of Regulation No. 11 of 2000 on the policy setting and street vendors development at Village Karangtempel Eastern District of Semarang can run effectively and efficiently.